Determination of volatile fatty acids in municipal wastewater by gas chromatography-mass spectrometry preceded by headspace- solid phase microextraction with PDMS-CAR fibre - Pokhrel, Teeka Ram (2010)
An analytical procedure based on headspace – solid phase microextraction (HS-SPME) followed by gas chromatography-mass spectrometry (GC-MS) has been developed for the determination of free volatile fatty acids in municipal wastewater samples. Polydimethylsiloxane-Carboxen (PDMS-CAR) fibre was found to have greater affinity to extract lower chain fatty acids. Extraction and gas chromatographic parameters of importance such as desorption time, sample volume, amount of salt to be added and extraction time have been optimized. Detection limits were in the low to medium mg/L levels. To evaluate the applicability of the developed HS-SPME procedure on real samples, municipal wastewater treatment plant samples were analysed.